2017
DOI: 10.1152/jn.00813.2016
|View full text |Cite
|
Sign up to set email alerts
|

Increased neuromuscular consistency in gait and balance after partnered, dance-based rehabilitation in Parkinson’s disease

Abstract: Here we examined changes in muscle coordination associated with improved motor performance after partnered, dance-based rehabilitation in individuals with mild to moderate idiopathic Parkinson's disease. Using motor module (a.k.a. muscle synergy) analysis, we identified changes in the modular control of overground walking and standing reactive balance that accompanied clinically meaningful improvements in behavioral measures of balance, gait, and disease symptoms after 3 wk of daily Adapted Tango classes. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
111
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(124 citation statements)
references
References 59 publications
7
111
3
3
Order By: Relevance
“…Indeed, we recently observed greater motor module consistency and distinctness during a balance-challenging walking behavior among expert professional ballet dancers compared with novice nondancers (Sawers et al 2015). Similarly, we found that improved gait and balance performance after rehabilitation in individuals with Parkinson's disease was associated not with increased module complexity but increased consistency and distinctness (Allen et al 2017). Although it is well-established that stroke survivors walk with increased step-to-step variability (e.g., spatiotemporal variability, Balasubramanian et al 2009), whether reduced motor performance is stroke survivors is accompanied by reduction in motor module consistency and distinctness is unknown.…”
Section: Introductionsupporting
confidence: 56%
See 3 more Smart Citations
“…Indeed, we recently observed greater motor module consistency and distinctness during a balance-challenging walking behavior among expert professional ballet dancers compared with novice nondancers (Sawers et al 2015). Similarly, we found that improved gait and balance performance after rehabilitation in individuals with Parkinson's disease was associated not with increased module complexity but increased consistency and distinctness (Allen et al 2017). Although it is well-established that stroke survivors walk with increased step-to-step variability (e.g., spatiotemporal variability, Balasubramanian et al 2009), whether reduced motor performance is stroke survivors is accompanied by reduction in motor module consistency and distinctness is unknown.…”
Section: Introductionsupporting
confidence: 56%
“…To date, motor module analysis for lower limb muscle coordination post-stroke has primarily focused on the number of motor modules recruited during gait behaviors. We recently utilized novel metrics of motor module consistency, distinctness, and generalization to examine other features of muscle coordination and identified differences related to gait and balance performance in both healthy adults (Sawers et al 2015) and individuals with Parkinson's disease (Allen et al 2017). However, it remains unclear how these modular features of muscle coordination are affected after stroke.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We were somewhat surprised that we did not find that antagonist activity in MG was abnormal in PD at the group level in this sample, given that we have previously reported excessive MG antagonist activity during balance tasks using a similar paradigm in PD patients in the ON medication state. 80 However, in a subsequent extensive examination of the activation of 6 muscles throughout the leg performed on a subset of these data, we found that the presence of PD was associated with elevated antagonist activity across generally all muscles examined, but that when muscles were considered in isolation, the effect was statistically significant only in TA. Here, although some patients exhibited strong antagonist activity in MG (see Figure S2, upper panel), others exhibited very little antagonist activity (see Figure S2, lower panel).…”
Section: Examples Of Antagonist Activity In Mgmentioning
confidence: 78%